Model Pengembangan Motif dan Produk Fesyen Batik berbasis Partisipasi di Batik Wardana Sragen - Sulistyati, Apika Nurani; Darwoto, Darwoto; Farikha, Alfi Yusrina; Widyastuti, Theresia (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: One of the shortcomings of small businesses in the field of batik-patterned textile production is the lack of ideas and skills in designing patterns, as well as the difficulty in improving the products. This program aims to expand the insights and skills of small and medium-sized enterprises (SMEs) so that they can further improve and enrich the styles of batik-patterned textile products with new creative designs and produce current fashion products for the women's market. Method: (1) initial observation and interviews; (2) program socialization, pre-test, and material presentation on motif styling, fashion product development for adult women, and its marketing strategy; (3) technical training on pattern design development; and (4) post-test, monitoring, and evaluation in the form of a discussion forum between the community service team and the owners and employees of Batik Wardana. Results: (1) An increase in employees' design skills in accommodating motif ideas and adapting them to market tastes; (2) mastery of digital batik motif creation techniques; (3) the ability to develop fashion products other than men's shirts, such as blouses or women's tops; (4) the ability to analyze market demand for current women's fashion products. The improvement was measured descriptively using pre- and post-tests. The results of the activity showed an increase in participants' descriptive understanding scores from an average of 42.0 to 83.0 after the training. Conclusion: Development of a design-based community service model that combines the principles of MSME empowerment, design creativity theory, and experiential learning.